Changes in Japan's inter-regional business linkage structure - Makoto Tsukai; Makoto Okumura (European Regional Science Association (ERSA), 2003)
In 1990's, Japan's domestic transportation and telecommunication service had been improved, and concurrently the knowledge-intensive business, which requires the intensive communication, becomes much important in economic activities. Improvement in communication technology would influence in two different ways, on inter-regional business linkages made up for the knowledge-intensive interaction. One is to increase the interaction along the conventional linkages based on geographic adjacency. The other is to directly connect the distant regions, resulting in pulling out of branch offices in intermediate regions, so called as 'straw effect?. In addition, a possibility of further change in business linkage on which transportation accessibility in geography is not important, so called as ?foot-loose economy?, is pointed out. Later two effects must be carefully considered in long-term regional planning. However, they have been proposed intuitive way, lacking theoretical or empirical bases. The empirical analysis based on statistical modeling is necessarily to clarify the fact. This study estimates Japan's inter-regional business linkage structure based on inter-regional information traffic data. The proposed model system consists of three sub-models; gravity model, hierarchical branch-office location model, and media split model. Conventional geo-based linkages are described by gravity model. Straw effect is caused by nation-wide firm covering multiple regions with branch-offices. The hierarchical branch-office location model describes the business network covering nation-wide regions. This model is based on a minimization of total cost of branch-office location and communication cost reflecting a unit cost estimated in media split model. Given a headquarter region and the index of branch-office function, this sub-model outputs some possible business linkage patterns of nation-wide firms. In order to estimate the effective cost for inter-regional communication, media split between transportation and telecommunication is modeled. Since inter-regional information traffic data (transportation and telecommunication) includes both conventional geo-based linkages, and business linkage patterns of nation-wide firms, we can simultaneously estimate both the gravity model for conventional geo-based linkages and the weights of business linkage patterns of nation-wide firms among possible patterns, so that those information flows match to the observed traffic data. This model can capture a cross-sectional business linkage structure. Therefore, we repeatedly applied the system for 1990 and 1995, and compared the estimated structures in order to clarify longitudinal change. Following results were obtained. Comparing in estimated weights of network patterns, the total sum of interactions on business linkage of nation-wide firms was decreased. The pattern with Tokyo headquarter(the capital of Japan) was decreased, instead of increased weight of Fukuoka and Miyagi headquarter(regional principal). Interactions between headquarter and branch-office became much knowledge-intensive than before, together with the enhancement of branch-office function. Branch-offices became to concentrate on transportation-hub cities. These results suggest that inter-regional communication on conventional geo-based linkages was increased, along with the straw effect on business networks of nation-wide firms. However, the further change such as ?foot-loose economy? did not occur in early ?90s.
Keywords: 330